Binding Mode and Structure–Activity Relationships of ITE as an Aryl Hydrocarbon Receptor (AhR) Agonist. (23rd January 2018) - Dolciami, Daniela; Gargaro, Marco; Cerra, Bruno; Scalisi, Giulia; Bagnoli, Luana; Servillo, Giuseppe; Fazia, Maria Agnese Della; Puccetti, Paolo; Quintana, Francisco J.; Fallarino, Francesca; Macchiarulo, Antonio
Abstract: Discovered as a modulator of the toxic response to environmental pollutants, aryl hydrocarbon receptor (AhR) has recently gained attention for its involvement in various physiological and pathological pathways. AhR is a ligand‐dependent transcription factor activated by a large array of chemical compounds, which include metabolites ofl ‐tryptophan (l ‐Trp) catabolism as endogenous ligands of the receptor. Among these, 2‐(1′ H ‐indole‐3′‐carbonyl)thiazole‐4‐carboxylic acid methyl ester (ITE) has attracted interest in the scientific community, being endowed with nontoxic, immunomodulatory, and anticancer AhR‐mediated functions. So far, no information about the binding mode and interactions of ITE with AhR is available. In this study, we used docking and molecular dynamics to propose a putative binding mode of ITE into the ligand binding pocket of AhR. Mutagenesis studies were then instrumental in validating the proposed binding mode, identifying His 285 and Tyr 316 as important key residues for ligand‐dependent receptor activation. Finally, a set of ITE analogues was synthesized and tested to further probe molecular interactions of ITE to AhR and characterize the relevance of specific functional groups in the chemical structure for receptor activity. Abstract : Binding modes : ITE is an endogenous product ofl ‐tryptophan catabolism. It is also a nontoxic aryl hydrocarbon receptor (AhR) agonist endowed with immunomodulatory properties. We used docking and molecular dynamics to investigate the binding mode of ITE into the ligand binding pocket of AhR. Mutagenesis studies were instrumental to validate the proposed binding mode, identifying His 285 and Tyr 316 as key residues for ligand‐dependent receptor activation. ITE analogues were also synthesized to develop a pharmacophoric model of relevant interactions with AhR.